RISK FACTORS OF STROKE AND THE HUMANIZATION OF NURSING CARE - da Silva Fonseca Lima, Gabriely; Aparecida Borges, Mariana; Helena Brizido Marinho Barreto, Maria (Health and Society, 2023)
Objective: To analyze through a literature review, CVA’S risk factors, nurse’s role in the preparation of the patient’s therapeutic plan after a CVA, the importance of Family support in client’s recovery, as well as the feelings experienced by informal carers. Method: This literature review is the search strategy for selecting articles from the Virtual Health Library databases. Results: Twelve studies were found, the final sample being 8 selected articles, with the criterion of nursing care with the patient after CVA, family support in recovery and risk factors for the pathology. Conclusion: The CVA victim transitions from an autonomous life to dependence on activities of daily living, and is inserted into a new routine of adaptations, generating worries and stress. In this way, the family is fundamental in the patient’s recovery, as it provides emotional support and hope for the client.